Seed Producer Organization of Farmer: An Experience of Western Terai, Nepal - Dhakal, S (Agronomy Journal of Nepal, 2013)
Use of improved seeds has a vital role in enhancing agricultural production. Agriculture extension has implemented farmers’ managed seed multiplication program at the community level to ensure efficient supply of improved seeds. Several success and failure cases of seed multiplication through farmers' organizations were experienced. Therefore, a case study was conducted in the western terai region of Nepal to explore the factors responsible for success/failure of farmers' organizations involved in seed production. The results of the study found that internal factors of group, nature of extension support, quality control mechanism, and seed marketing approaches are the key elements, which affect the performance of farmers' organizations- seed groups and cooperatives. It was also observed that organizations developed in farmers' own initiatives performed better than those formed in external influence. The results of this research suggest that the autonomy of group actions has long term impact on ownership development. Business skills, technical skills and organizational management skills were equally important for the viability of farmers' organizations so far as seed business is concerned. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 156-167 DOI: http://dx.doi.org/10.3126/ajn.v3i0.9018